ANALISIS EFEKTIVITAS PEMUNGUTAN PAJAK HOTEL DAN PAJAK RESTORAN SERTA KONTRIBUSI TERHADAP PENDAPATAN ASLI DAERAH KOTA TOMOHON - Anggraini, Ni Luh Putu; Tinangon, Jantje J.; Walandouw, Stanley Kho (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The Local Genuine Income (PAD) is a income earned by the region through regional taxes, regional retribution, and management of regional wealth for the development of the region. The hotel and restaurant tax is the local tax that has the potential to improve local revenue due to the supporting component from tourism sector Tomohon City which keep growing. The purpose of this study is to determine the level of effectiveness of hotel tax and restaurant tax collection in Tomohon City in 2013-2017 and to find out the contribution given by hotel tax and restaurant tax on the receipt of original revenue in the city of Tomohon in 2013-2017. The method used in this thesis is descriptive method, that is by analysing data and then drawing conclusion from the results of the study and the type of research used is descriptive qualitative. The results of this study indicate that the effectiveness of hotel tax collection in 2013-2017 has been effective with an average of 90,40%, while the effectiveness of restaurant tax is very effective with an average of 132,94%. The contribution given by the hotel tax to the local revenue of Tomohon city in 2013-2017 is still very lacking with an average of 0,60%, while the contribution given by the restaurant tax is not good with an average of 12,33%. Keywords : Hotel Tax, Restaurant Tax, Contribution, Effectiveness, Local Genuine Income